PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN QUESTION BOX TERHADAP HASIL BELAJAR SISWA PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN KELAS XI IPA MAN 1 PONTIANAK - Puspa Sari; Tuti Kurniati; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThe low level of students’ learning outcomes at MAN 1 Pontianak on solubility and the result of solubility multiply was caused by lack of students’ understanding on basic concept. This research had the purpose to find out the difference between the students’ learning outcomes which were taught by using Teams Games Tournament (TGT) type of Cooperative Learning Method Assisted Question Box and the lectures teaching method assisted Question Box as well as to know the effect of TGT type of Cooperative Learning Method Assisted Question Box. This research was Quasi Experimental Control Pretest Posttest Group Design. The sampling system was simple random sampling technique. The techniques of data collection used measurement technique, observation and direct communication (interview). The result of data analysis showed that the mean score of experimental class was 73.8 which was higher compared to the mean score of control class which was 62.97. The result of statistical analysis using U-Mann whitney test with α 5% obtained 0.00 value which was smaller than α value (0.00 <0.05). It meant that there was difference between the learning outcomes in experimental and control class. The calculation result using effect size showed the value of ES 0.91 which was included in high category. It could be concluded that TGT type of Cooperative Learning Method assisted Quesion Box gave high effect on the improvement ofstudents’ learning outcomes which was 31.86 %. Keywords: Learning Outcomes, Solubility and The Result of Solubility Multiply, TGT, QuestionBox